Phenotypic Confirmation of Extended-Spectrum B-Lactamases (ESBL) in Clinical Isolates of Escherichia coli and Klebsiella pneumoniae at the San Juan Veterans Affairs Medical Center - Rodríguez, María del Carmen; Vera, Doris E.; Ramírez-Ronda, Carlos H.; Saavedra, Sonia (Puerto Rico Health Sciences Journal, 2010)
see manuscript